Investigations to improve CdTe-based solar cell open circuit voltage and efficiency using a passivation and selectivity theoretical framework - Reich, Carey, author; Sampath, Walajabad S., advisor; Holman, Zachary C., committee member; Kuciauskas, Darius, committee member; Sites, James R., committee member (Colorado State University. Libraries, 2022)
The voltage of CdTe-based solar cells has remained conspicuously low despite years of efforts focused directly on its improvement. The efforts here have been primarily in increasing the equilibrium carrier concentration of the CdTe or its alloys which are used to absorb the light. This direction has been guided by a theory of solar cells that views the cell only as a single p/n junction. The modelling which has been used to confirm this as an appropriate direction indicated that with a moderate carrier lifetime, relatively small front interface recombination velocity, and large equilibrium carrier concentration in the absorber, efficiencies greater than the current record of 22.1% will be possible with open circuit voltages reaching over 1V. However, cells with these properties have been measured and increases in Voc and efficiency have not been attained. In the c-Si community, notably, the "passivation – selectivity" framework has been developed. In particular, it rejects the view that a singular p/n junction is responsible for the function of a solar cell. Instead, this framework operates with the understanding that the potential in the cell which can be turned into useful electrical energy and an increase in open circuit voltage comes only from the excess carriers generated by sunlight forcing a deviation from the equilibrium condition. As such there are two main components: 1) passivation – which refers to the recombination behavior in the cell and development of a large internal potential difference and 2) selectivity – which refers to the asymmetry of conduction in the cell that allows for production of a unidirectional current and an external voltage approaching that within the cell. This framework tends to break the cell into 3, sometimes overlapping, regions: an absorber region that is used to produce as large a potential difference as possible, and two contact regions in which the transport properties are modified to prefer transport of one carrier or the other. Here this framework is applied to CdTe-based solar cells to determine what limits current cells and how to overcome these limitations. In the investigation of passivation, first the electron contact interface is evaluated, resulting in the determination that this interface is not currently limiting the recombination in the cell. As a result, the current baseline is compared to structures hypothesized to provide improvement in the recombination behavior. It is found that cells with CdSeTe as the only material in the bulk exhibit more ideal recombination behavior when compared to a CdSeTe/CdTe structure as is currently used. This comparison demonstrates a pathway for cells to overcome their current limitation due to recombination, with the possibility of reaching up to 25% efficiency and 970 mV Voc with the material that currently is produced at CSU. A native oxide of TeOx is found to passivate the surface, reducing the rate non-radiative recombination, and forms during dry air exposure, providing a pathway to passivate contacts that would be ideal if not for the recombination at the interface. In the investigation related to selectivity, the electron contact is evaluated and it is demonstrated that MgZnO is appropriately selective when deposited with the correct conditions. It therefore is expected that hole selectivity is the primary loss to open circuit voltage in structures determined to have longer excess carrier lifetimes and large radiative efficiencies. Efforts to investigate novel routes to hole selectivity by use of heterojunction contacts are presented. Such routes did not yield improvements in cell Voc and efficiency, and through this work it was determined that a major source of selectivity losses in these cells is the high resistance to hole transport through the bulk semiconductor. Increasing hole concentration or thinning the absorber provide pathways to overcome this specific limitation, but it is modelled that such cells will require structures with hole selective materials that internally cause a reduction of electron current to see improvement in Voc and efficiency.
Keywords: open circuit voltage; selectivity; passivation; CdTe